Vitamin D in 2020 Stop or Not Yet? - Courbebaisse, Marie; Cavalier, Etienne (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Many things have been said and written on the skeletal and non-skeletal effects of vitamin D, but the largest recent interventional studies are generally negative. How should we thus position ourselves in 2020? Should we say "stop" or "not yet"? Indeed, the aging of the population, as well as new challenges and discoveries, is still triggering interest in this old molecule. In this Special Edition of Nutrients, we invited top experts to give their opinion on this important debate. We also encouraged scientists to submit their latest research on nutritional requirements in the general population and in high-risk groups, as well as treatment strategies, epidemiology, analytical updates and new devices for vitamin D measurement and the effect of vitamin D on bone and extra-skeletal health. As readers will see, this Special Issue reinforces the high prevalence of vitamin deficiency and insufficiency in the general population and supports the safety of this low-cost molecule, revealing new perspectives regarding the extra-skeletal effects of vitamin D.